New Anode Material for Lithium-Ion Batteries: Aluminum Niobate (AlNb11O29) - Lou, Xiaoming; Li, Renjie; Zhu, Xiangzhen; Luo, Lijie; Chen, Yongjun; Lin, Chunfu; Li, Hongliang; Zhao, X. S (ACS applied materials & interfaces, 2019)
This paper describes the syntheses and electrochemical properties of a new niobate compound, aluminum niobate (AlNb11O29), for Li+ storage. AlNb11O29-microsized particles and nanowires were synthesized based on the solid-state reaction and solvothermal methods, respectively. In situ X-ray diffraction results confirmed the intercalating mechanism of Li+ in AlNb11O29 and revealed its high structural stability against cycling. The AlNb11O29 nanowires with a novel bamboo-like morphology afforded a large interfacial area and short charge transport pathways, thus leading to the observed excellent electrochemical properties, including high reversible Li+-storage capacity (266 mA h g–1), safe operating potential (around 1.68 V), and high initial Coulombic efficiency (93.3%) at 0.1 C. At a very high rate (10 C), the AlNb11O29 nanowires still exhibited a capacity as high as 192 mA h g–1, indicating their good rate capability. In addition, at 10 C, 96.3% capacity was retained over 500 cycles, indicating superior cycling stability. A full cell fabricated with AlNb11O29 nanowires as the anode and LiNi0.5Mn1.5O4 microparticles as the cathode delivered a high energy density of 390 W h kg–1 at 0.1 C. This work suggests that the AlNb11O29 nanowires hold a great promise for the development of high-performance lithium-ion batteries for large-scale energy-storage applications.